1992
DOI: 10.1109/20.179784
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different demagnetisation processes on interaction effects in thin film media

Abstract: Abrtmct -In thh papa the effects of different demagnetisation procasu on intaactionr in thin fikn media have been examined.InterrCtion &ectr are examined using the now well established 6 1 tachnique. Tht study giver a better understanding to the nature of intaactionr in thin film media and in particular the effect of the initial magnetic state on the 61 technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…18,19 The advantage of the FORC method over other approaches is the extreme sensitivity to microscopic details of hysteretic systems. Although the wealth of information a FORC diagram delivers still remains to be fully characterized, the method can be used as an extremely sensitive "fingerprint" of a hysteretic system.…”
Section: Outline Of the Forc Methodsmentioning
confidence: 99%
“…18,19 The advantage of the FORC method over other approaches is the extreme sensitivity to microscopic details of hysteretic systems. Although the wealth of information a FORC diagram delivers still remains to be fully characterized, the method can be used as an extremely sensitive "fingerprint" of a hysteretic system.…”
Section: Outline Of the Forc Methodsmentioning
confidence: 99%
“…A different approach, based on simulated annealing, has been used by Dean et al [83] to produce the ac erased state. A recent study [84] has shown that the IRM curve is very strongly dependent on the details of the erasure process. the lowest energy state of the system.…”
Section: Remanence Curve Studiesmentioning
confidence: 99%
“…2. Compositions of films were examined with an EDX spectrometer, and the magnetic properties including the magnetization M , coercivity H c , intergrain interaction behavior ⌬M , 3 and the magnetic switching volume or magnetic grain, 4,5 were measured with an alternating gradient force magnetometer.…”
Section: Methodsmentioning
confidence: 99%